PERLINDUNGAN KORBAN SALAH TANGKAP PADA PEMBERANTASAN TINDAK PIDANA TERORISME POSO - Tahir, Febriansyah (Katalogis, 2015)
Febriansyah, Protection to False Arrest Victims in Poso Terrorism Crime Banning. The research was to study protection to false arrest victims in Poso terrorism crime banning and legal sanctions to officer falsely arresting officers. Theoretically/academically, the research findings were supposed to contribute to development of science of law, specifically criminal law. Practically, they were supposed to serve as a platform for further researches and supply with descriptions and constructive thoughts for decision makers in coping with arising problems. It is the authority of a court of the first instance to hear and judge pre-judicial cases to sentence whether or not an arrest, imprisonment, cease of investigation or litigation, reimbursement and/or rehabilitation of one whose criminal case is ceased while it is in an investigation phase. In case the verdict on a pre-judicial case is in favor of a victim by a judge hearing and judging it, the false arrest victim by police officers shall be entitled to get reimbursement and rehabilitation as provided the Article 95 and Article 97 of the Indonesian Criminal Code. The officers falsely arresting a victim shall be subject to disciplinary sanctions for breaching Article 4 letter d and Article 5 letter a of the Indonesian State Regulation Number 2 Year 2003 about Disciplinary Regulations for Indonesian Police Officers. The sanctions shall cover indisciplinary proceedings suspended rank promotion for 2 period, demotion from a detective to a staff officer, and placement in a special space for 21 days.